PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP KEMAMPUAN BERHITUNG PADA MATERI PENJUMLAHAN KELAS I SDN 010 SIABU - Liana Azara Rossa; Muhammad Syahrul Rizal; Dwi Viora; Yenni Fitra Surya; Zulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Background This research is motivated by the low arithmetic ability of first grade students of SDN 010 Siabu, especially in addition material. This is caused by the use of conventional learning methods that are less interesting and the lack of utilization of concrete learning media. This study aims to determine the effect of using the jarimatika method on students' arithmetic ability in addition material. The research method used is a quasi-experimental design with a non-equivalent control group design. The research sample consisted of two classes, namely class I A as the experimental group and class I B as the control group, each consisting of 21 students. The instrument used was a numeracy ability test that had been tested for validity and reliability. The results of data analysis using the independent t-test showed that there was a significant difference between the posttest scores of the experimental group and the control group, with a significance value of 0.001 <0.05. The average posttest score of the experimental group was higher, namely 89.05 compared to the control group 80.90. Based on these results, it can be concluded that the use of the jarimatika method has a positive effect on improving the arithmetic ability of first grade students in addition material. Keywords: Jarimatika Method, Arithmetic Ability, Addition and Elementary School Students